2018
DOI: 10.3389/fmars.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Futures Under Ocean Acidification, Marine Protection, and Changing Fishing Pressures Explored Using a Worldwide Suite of Ecosystem Models

Abstract: Ecosystem-based management (EBM) of the ocean considers all impacts on and uses of marine and coastal systems. In recent years, there has been a heightened interest in EBM tools that allow testing of alternative management options and help identify tradeoffs among human uses. End-to-end ecosystem modeling frameworks that consider a wide range of management options are a means to provide integrated solutions to the complex ocean management problems encountered in EBM. Here, we leverage the global advances in ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 121 publications
1
46
0
Order By: Relevance
“…The sophistication of EwE with Ecospace and Atlantis allows these modeling approaches to tackle a wide number of EBFM issues, including MPA effectiveness (e.g. Salomon et al 2002, Martell et al 2005, Savina et al 2013, Olsen et al 2018, the consequences of bycatch reduction measures (e.g. Fulton et al 2007, Walters et al 2010, Morzaria-Luna et al 2012, 2013, and management strategy evaluations integrating ecosystem considerations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The sophistication of EwE with Ecospace and Atlantis allows these modeling approaches to tackle a wide number of EBFM issues, including MPA effectiveness (e.g. Salomon et al 2002, Martell et al 2005, Savina et al 2013, Olsen et al 2018, the consequences of bycatch reduction measures (e.g. Fulton et al 2007, Walters et al 2010, Morzaria-Luna et al 2012, 2013, and management strategy evaluations integrating ecosystem considerations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9). A recent paper assessing the effect of MPAs across multiple Atlantis ecosystem models, including the Northern GOC model, also found that MPAs led to both 'winners' and 'losers' at the level of particular species or functional groups (Olsen et al 2018).…”
Section: Climate Change Adaptationmentioning
confidence: 95%
“…of these un-vetted indicators (Houle et al, 2012;Ortega-Cisneros et al, 2018;Shin et al, 2018). Fulton et al (2005), Samhouri et al (2009), Kaplan et al (2013), Olsen et al (2018) and Ortega-Cisneros et al (2018) used endto-end model simulations to examine the impacts of fishing and climate on indicators. In these studies model simulations were projected at different levels of fishing or environmental variability and indicators were calculated from these outputs and examined against ecosystem attributes (to examine validity and sensitivity) or pressures (specificity).…”
Section: Value Of Using End-to-end Models For Indicatorsmentioning
confidence: 99%